THE CURRENT STATE OF INDEPENDENT WORK OF FUTURE QUALIFIED WORKERS IN THE CONDITIONS OF MIXED EDUCATION IN WARTIME (Innovative professional education, 2023)
Independent work of future skilled workers is an integral part of blended learning. In the conditions of the information society, independent work is a multidimensional pedagogical phenomenon, which is not only a method or a means of learning, but is also one of the forms of educational activity of students on a level with classroom (auditory) education, and in times of limited access to face-to-face attendance at an educational institution, it becomes the main means of mastering educational theoretical material.
Keywords: independent work, blended learning, future skilled workers